Building a Data Warehouse - Rainardi, Vincent (Apress, 2012)
Friends and colleagues who want to start learning data warehousing sometimes ask me to recommend a practical book about the subject matter. They are not new to the database world; most of them are either DBAs or developers/consultants, but they have never built a data warehouse. They want a book that is practical and aimed at beginners, one that contains all the basic essentials. There are many data warehousing books on the market, but they usually cover a specialized topic such as clickstream, ETL, dimensional modeling, data mining, OLAP, or project management and therefore a beginner would need to buy five to six books to understand the complete spectrum of data warehousing. Other books cover multiple aspects, but they are not as practical as they need to be, targeting executives and project managers instead of DBAs and developers. Because of that void, I took a pen (well, a laptop really) and spent a whole year writing in order to provide a practical, down-to-earth book containing all the essential subjects of building a data warehouse, with many examples and illustrations from projects that are easy to understand. The book can be used to build your first data warehouse straightaway; it covers all aspects of data warehousing, including approach, architecture, data modeling, ETL, data quality, and OLAP. I also describe some practical issues that I have encountered in my experience—issues that you’ll also likely encounter in your first data warehousing project— along with the solutions.